ROUND CELL MALIGNANCIES OF ORAL AND MAXILLOFACIAL REGION- AN OVERVIEW - SANKARI, DR. S.LEENA; N, VAISHNAVI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Round cell tumors comprises of a wide group of malignancies predominantly affecting the children and adolescents. They include various malignancies of epithelial, neuroectodermal, lymphoreticular and mesenchymal origin. They are referred to as round cell tumors because they present themselves as small, relatively undifferentiated proliferation of round cells with higher nuclear hyperchromatism and increased nuclear cytoplasmic ratio in light microscopy. The diversity of the lesion and their uniform morphological appearance poses a great diagnostic challenge for the pathologist. Recently, with addition of cytogenetic, the diagnosis has been made quite easy for the pathologist. Adjuvant diagnostic parameters include immunohistochemistry, comparative genomic hybridization, polymerase chain reaction and fluorescence in situ hybridization. This article briefly reviews the various aspects of round cell tumors occurring in the maxillofacial region.